(untitled) (Atti del Sodalizio Glottologico Milanese, 2018)
Gioachino Belli’s “Introduction” to his poems offers an intriguing example how Dante’s linguistic approach to the poetical matter can affect a XIX century Italian poet. The relation between the “Introduction” and “De vulgari eloquentia” is here detected on the base of parallelisms within a shared interpretation of the sharp opposition affecting language skills acquired in a natural way or a language achievement assumed in the school environment. KEYWORDS: language variation within Italian; written and common language; poetical matters; natural linguistic skills; achievements of language levels